Developing a Treatment-Resistant Depression Consultation Program, Part II: Assessment - Fournier, Jay C; Voytenko, Vitaliy L; Docherty, Anna R; Wright, Jesse H; Virk, Subhdeep; Riva Posse, Patricio; Flood, Michael J; Quevedo, Joao; Burnett, Diana K; Bobo, William V; Conroy, Susan K; Parikh, Sagar V (The journal of clinical psychiatry, 2025)
To provide recommendations regarding the critical elements of the assessment package in treatment-resistant depression (TRD) consultation programs. This is a complementary manuscript to Part I, which discusses practical and logistical considerations for developing and sustaining a subspecialized TRD consultation program. A group of 12 clinicians, researchers, administrators, and patient advocates from the National Network of Depression Centers (NNDC) TRD Task Group. The recommendations are based on expert opinion. This consensus statement reflects the effort of the NNDC's TRD Task Group to reach agreement on a set of principles that those interested in establishing new consultation programs could use to guide their effort and a set of recommendations that could serve as a basis for future empirical work. Each member of the NNDC TRD Task Group provided a written description of the procedures used at their home institution, which were used during a day-long forum to achieve consensus on recommendations for each component of a TRD consultation program. Subgroups were formed to draft recommendations, and points of disagreement were resolved at subsequent meetings of the full task group. We describe consensus recommendations regarding the goals of a TRD consultation, which include establishing the primary diagnosis and comorbidities, clarifying medical and psychiatric symptoms, identifying goals, documenting treatment history, identifying treatment barriers, and developing actionable treatment recommendations. We detail important components of the consultation evaluation process, the assessment tools to consider in establishing a TRD consultation program, and the qualifications of providers.